Identification of herbicide resistance loci using a genome-wide association study and linkage mapping in Chinese common wheat - Chaonan Shi; Yueting Zheng; Junyou Geng; Chunyi Liu; He Pei; Yan Ren; Zhongdong Dong; Lei Zhao; Ning Zhang; Feng Chen (Crop Journal, 2020)
Carfentrazone-ethyl and tribenuron-methyl, the two widely used herbicides for weed control in field crops, frequently cause phytotoxicity to wheat seedlings in the field. In this study, a total of 697 wheat accessions containing three panels were scanned using wheat 90 K and 660 K SNP arrays to identify important herbicide resistance loci. Genome-wide association study (GWAS) revealed 329 significant single-nucleotide polymorphisms (SNPs) with phenotypic variance explained (PVE) of 11.3% to 27.6%. Among these SNPs, 15 were detected in multiple environments and they were mainly distributed on chromosomes 1B, 2D, 5B, 5D, 6D, and 7D. Further analysis indicated that gHR-5B (467–587 Mb), gHR-7D (46–52 Mb), and gHR-1B (517–580 Mb) were important herbicide resistance loci in wheat. Linkage mapping in a bi-parental population detected one QTL (qHR-1B) with PVE of 7.44% to 8.28%. This is reliable locus because its physical position (554–566 Mb) overlapped with gHR-1B by GWAS in the genome of Chinese Spring. This study provided some herbicide-resistant germplasm and important genetic loci for identifying genes of common wheat.